Badjao the sea gypsies - Bayer, Rolf
Hassan, the son of a tribe chief of the Badjao's, a pagan, sea-dwelling Filippino tribe, meets and falls for Bala-amai, the niece of the chief of the Moros, an Islamic, land-dwelling tribe. Although the Hassan is willing to give up his lifestyle for Bala-amai and vice versa, the Moros plot to break up the union of the happy couple.--Anonymous.